Instant payments and brazilian pix: lessons from the indian experience in the 2010’s - Camacho, Tatiana Silveira; Silva, Guilherme Jonas Costa da Silva (Brazilian Keynesian Review, 2024)
Instant payments are part of an ecosystem of financial innovations, promoting quick and easy access to funds. Through Nonlinear Distributed Lag Autoregressive Models (NARDL), this article aims to draw lessons from the Indian experience with the Unified Payments Interface (UPI), for the Brazilian Pix. The empirical results show that the substitutes for instant payments (credit and debit cards) have a complementary character, while the measure of relative popularity of mobile banking (MB/WLESS) and degree of sophistication of the financial system (M1/GDP) has immediate effects on these flows. Short-term negative asymmetric shocks had greater impacts on instant payment systems.